The impact of social and security factors on residential site suitability by using GIS-based MCDM approach: a case study the city of Kirkuk, Iraq - Abdula, Mazen Abdilwahab; Mohd Yusof, Mohd Johari; Abu Bakar, Shamsul; Ahmad, Noordin; Abdullahi, Saleh; Omer, Najat Qader (Faculty of Design & Architecture, Universiti Putra Malaysia, 2015)
Unplanned population growth, alongside unplanned development, lack of good housing and inadequate infrastructure resulted in a lot of slums and informal settlements in Iraqi cities. In 1980s there were major housing shortage in Iraq as a result of war and political instability which led to economic meltdown. Kirkuk city was one of the most affected cities by multiethnic crises as a result of employment, housing and local government members’ concentration in Kirkuk which led to political and economic migration. Suitable site selection for housing is complicated not just because it has to do with technical procedures and topography but due to environmental, social and political issues which can lead to conflict. Hence, this study seeks to discover the suitable site selection for housing using Geographical Information System (GIS), high resolution remote sensing data and multi criteria analysis (MCA).